Watertight Soil-Cement Dump of Oil and Gas Industry Waste - Zotsenko, Mykola; ., Yuriyvynnykov; Lartseva, Iryna (International Journal of Engineering and Technology, 2018)
It is established that the most accessible way of isolation of toxic wastes formed during drilling, development, exploitation and treatment of oil and gas wells products is to dispose them directly in the earth's slime dumps on the territory of the drilling site or beyond. The dumpâ€™s pit must have a watertight protective diaphragm, which is durable and resistant to the aggressive effects of toxic waste drilling and exploitation of oil and gas wells. The chemical composition of the borehole mud is determined. The results of experimental laboratory researches of borehole mud aggressive components influence on the physical and mechanical watertight diaphragm characteristics are given. The geotechnical parameters of soil-cement were analyzed with the aim of its application for the arrangement of toxic waste watertight dumpâ€™s diaphragm.Â Â